O22.6 Field Evaluation of Three Point-Of-Care Tests For Chlamydia and Gonorrhoea in Remote Health Services in Australia. (13th July 2013) - Causer, L M; Hengel, B; Natoli, L; Tangey, A; Badman, S; Tabrizi, S N; Whiley, D; Ward, J; Kaldor, J M
Abstract : Introduction: Control of sexually transmissible infections (STIs) can be compromised by delays in time to diagnosis and treatment. Point-of-care (POC) tests can provide results at time of consultation. We conducted field evaluations of three POC tests (one new molecular-based and two best-performing immunochromatographic tests [ICT] identified from preliminary laboratory evaluations) for diagnosis of gonorrhoea (NG) and chlamydia (CT) at selected remote health services in Australia to identify the most suitable device for a larger randomised trial. Methods: Urine specimens collected from patients attending health services for routine STI screening were aliquotted and tested onsite with: GeneXpert ® CT/NG (simultaneous detection of CT and NG), Diaquick CT (CT only), and Gonorrhea Card (NG only). We compared results to routine laboratory reference results (commercial nucleic-acid amplification test) and calculated sensitivity (Sn) and specificity (Sp) by standard methods. We assessed selected operational characteristics. Results: For GenXpert (n = 99): Sn and Sp for CT were: 100% (95% confidence interval [CI]: 56.1–100) and 98.9% (CI: 93.1–99.9); for NG: 100% (CI: 56.1–100) and 100% (CI: 95.0–100). For Diaquick (n = 50), Sn and Sp were: 42.9% (CI: 11.8–79.8) and 97.7% (CI: 86.2–99.9). For Gonorrhea Card (n = 15), Sn and Sp were: 66.7% (CI: 12.5–98.2) and 75.0% (CI: 42.8–93.3). Urine volume required: GeneXpert = 1ml; both ICTs = 15ml. Mean preparation time: GeneXpert = 1 minute and ICTs = 18 minutes. Time to result: GeneXpert = 88 minutes, Diaquick = 10 minutes and Gonorrhea Card = 15 minutes. Results from additional evaluation sites occurring in early 2013 will also be presented. Conclusions: The GeneXpert is highly accurate for detection of CT and NG from urine in these field settings. Similar performance has been reported from the laboratory. Despite longer time to results than traditional ICTs, the exceptional accuracy and operational benefits makes the GeneXpert device appealing for use where delays to treatment are frequent. This device will be further evaluated in a cluster-randomised controlled trial (TTANGO) to commence mid-2013.